Implementasi Pengendalian Quadcopter Dengan Prinsip Virtual Reality Menggunakan Google Cardboard - Dimas Angger Pribadi; Eriq M. Adams Jonemaro; Gembong Edhi Setyawan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Quadcopter is an RC Craft that is in great demand by humans both in personal use, or used as a research object for the development of quadcopter technology. One type that is often used as the obÂject of research is Parrot AR.Drone. Parrot AR.Drone is a device that can be controlled by using android smartphone, where other drones still use the remote control. In addition to using android, Parrot AR.Drone can also be controlled by using other devices such as kinect, joystick, oculus rift and much more. This is because Parrot AR.Drone is an open source that can be developed by everyone. The author's interest in this research is to control Parrot AR.Drone with the principle of virtual reality using head movement. The purpose of this research was to create a quadcopter control program using head movement input with google cardboard device, which will provide first person view (fpv) experience to the user as if the user is in the quadcopter. In this research, google cardboard is used as a virtual reality support device to control the movement of Parrot AR.Drone. The result of this research is the quadcopter drone control program using head movement. Testing phase is done by testing each head movement to find out the response of Parrot AR.Drone movement. Based on the results of the tests conducted, obtained the result of control accuracy level is 97%, and different response times of drone movement when controlled.